PENGARUH LITERASI KEUANGAN DAN AKSES MODAL TERHADAP KINERJA UMKM DENGAN DIGITALISASI SEBAGAI VARIABEL MODERASI : (Studi pada UMKM Kabupaten Bantul Daerah Istimewa Yogyakarta) - Maria Yosefina Fono; Mega Handayani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2026)
This study aims to analyze the influence of financial literacy and access to capital on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Bantul Regency, and to examine the role of digitalization as a moderating variable. A quantitative approach was employed using primary data collected through questionnaires distributed to 399 MSME actors. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. The sampling method applied was simple random sampling. The results indicate that financial literacy has a positive and significant effect on MSME performance. Conversely, access to capital has a negative but significant effect. Digitalization does not moderate the relationship between financial literacy and MSME performance; however, it moderates the effect of access to capital on performance. These findings highlight the strategic role of digitalization in enhancing external factors particularly access to capital in improving MSME performance. Keywords: Financial Literacy, Access to Capital, Digitalization, MSME Performance.